DETERMINATION OF LETHAL AND SUB-LETHAL CONCENTRATIONS OF DELTAMETHRIN IN JUNDIA (RHAMDIA QUELEN) Determinação das concentrações letal e subletal de deltametrina em Jundiá (Rhamdia quelen) - do Amaral Gurgel Galeb, Luciana; Fredianelli, Ana Carolina; Pizzolato Montanha, Francisco; Mikos, Jorge Daniel; Pinto D’Amico Fam, Ana Laura; Mangrich Rocha, Rita Maria; Gaberz Kirschnik, Peter; Weber, Saulo Henrique; Turra Pimpão, Cláudia (Revista Acadêmica Ciência Animal, 2013)
Introduction: Deltamethrin (DM) is a synthetic pyrethroid toxic to vertebrates and lethal to fish at concentrations one million times lower than to mammals. It can be easily absorbed by the gills even when at low concentrations in the water, which contributes to the increased fish sensitivity. Objective: Determine the lethal and sub-lethal concentrations of DM to Jundiá (Rhamdia quelen) during 96 hours of exposure. Materials and methods: The study used 108 Jundiá fish with an average weight of 40 ± 5 g. The experiment was executed in triplicate and each set of fish was submitted to one of the following conditions: control (0 mg.L-1) and eight concentrations of DM (0.1; 0.5; 1.0; 1.5; 1.7; 2.0; 2.3; 5.0 mg.L-1). Results: Themain toxic signs observed were alterations in the respiratory, nervous and integumentary systems. The sub-lethal concentration at 96 hours was between 1.0 and 1.5 mg.L-1 and the lethal concentration was 1.7 mg.L-1. Conclusion: DM shows toxicity to Jundiá when present at ≥ 1.0 mg.L-1 in water.